Association of oral tumor suppressor gene deleted in oral cancer-1 (DOC-1) in progression of oral precancer to cancer. Issue 1 (January 2015) - Katarkar, Atul; Patel, Leelavati; Mukherjee, Sanjit; Ray, Jay Gopal; Haldar, Pallab Kanti; Chaudhuri, Keya
Abstract: Introduction: Deleted in oral cancer-1 (DOC-1), a highly conserved tumor suppressor gene, encodes a specific cyclin-dependent kinase 2-associated protein 1 (p12 DOC-1 ). The protein DOC-1 arrests the cells in the G1 phase of the cell cycle and regulates DNA replication in the S phase of the cell cycle. It is known that DOC-1 is downregulated in head and neck cancer. Hence, the aim of the study was to analyze the messenger RNA (mRNA) expressions of DOC-1 in patients with oral lichen planus (OLP), leukoplakia (LPK), oral submucous fibrosis (OSF), and oral squamous cell carcinoma (OSCC) in comparison to normal control subjects, and these were correlated with differential oral habits and duration of exposure. Materials and methods: Semiquantitative one-step reverse transcriptase polymerase chain reaction (RT-PCR) was used to assess the potential role of DOC-1 in differential oral conditions. Results: The expression of DOC-1 at the transcriptional level was found to be consistently reduced (39.13%) or non-detectable (60.87%) in OSCC cases; LPK cases also showed reduced (26.19%) or non-detectable (59.52%) DOC-1 expression, and overexpression of DOC-1 was observed in patients with OSF (42.3%) and OLP (35.29%) as compared to the normal control groups. A marked reduction in DOC-1 expression was observed in patients who smoke bidi and chew tobacco compared to patients who smoke cigarettes and chew pan . An overall reduced expression of DOC-1 with an increase in the duration of exposure was observed. Conclusions: The overexpression of DOC-1 in oral premalignant disease groups with reduced or loss of expression in OSCC groups suggests its association in the progression of oral carcinogenesis, suggesting DOC-1 to be an important prognostic indicator for oral cancer.